Re-Imagining Economic Sociology - Aspers, Patrik; Dodd, Nigel (Oxford University Press, 2015)
The purpose of this book is to explore new developments in the field of economic sociology. It contains cutting-edge theoretical discussions by some of the world's leading economic sociologists, with chapters on topics such as the economic convention, relational sociology, economic identity, economy and law, economic networks and institutions. The book is distinctive in a number of ways. First, it focuses on theoretical contributions, by pulling together and extending what the contributors believe to be the most important theoretical innovations within their own particular areas of the field. Second, there are contributions by leading economic sociologists from both the US and Europe, which gives the book both wider scope and appeal, while also creating the opportunity for some interesting dialogue between distinct theoretical traditions. The book will be of interest to researchers, Ph.D. students, and advanced students on both side of the Atlantic, and indispensible in advanced economic sociology courses.
Sociology
Keywords: business & economics; economic sociology; economic theory; social science / sociology / general